Crystal structure and Hirshfeld surface analysis of 2-{[7-acetyl-4-cyano-6-hydroxy-8-(4-methoxyphenyl)-1,6-dimethyl-5,6,7,8-tetrahydroisoquinolin-3-yl]sulfanyl}-N-phenylacetamide - Eman M. Sayed; Reda Hassanien; Shaaban K. Mohamed; Joel T. Mague; Mehmet Akkurt; Nasser Farhan; Etify A. Bakhite; Safiyyah A. H. Al-Waleedy (Acta Crystallographica Section E: Crystallographic Communications, 2021)
The title molecule, C29H29N3O4S, adopts a conformation with the two phenyl substituents disposed on opposite sides of the mean plane of the isoquinoline unit. In the crystal, corrugated layers of molecules are formed by N—H...O, C—H...N and C—H...S hydrogen bonds together with C—H...π(ring) interactions. These layers are connected by C—H...O contacts. The Hirshfeld surface analysis of the crystal structure indicates that the most important contributions for the crystal packing are from H...H (45.2%), C...H/H...C (20.2%), O...H/H...O (15.8%) and N...H/H...N (11.0%) interactions.